PERTANGGUNGJAWABAN HUKUM DOKTER ATAS KESALAHAN DALAM MENDIAGNOSIS DALAM PELAYANAN MEDIS DI RUMAH SAKIT - Budiarsih Budiarsih (Jurnal MHKI, 2021)
Increasing technological innovation today continues to experience unstoppable developments. Likewise, in the world of health, this is in line with the paradigm of people's lifestyle that tries to get it in instant ways that have direct implications for the condition of the people's immune system. The lifestyle of society which has undergone drastic changes and has an impact on the community's immune system, has resulted in the potential for the district to experience an unacceptable condition which has made the development of medical solutions in the medical world experience extraordinary stories, in line with the actions to be taken by doctors. The focus of research is on how is the legal responsibility of doctors for in-hospital misdiagnosis services. The methods used in this research are normative jurisprudence and literature review approaches. The results of the study found that the responsibility of a doctor who has full access and control of the medical service process towards ethically accountable patients is presented to the Honorary Medical Ethics Council (MKEK) and in a broader context, the victim's family who feels harmed by all the actions taken by the doctor can take legal action both civil and criminal.